Pola Asupan Gizi Anak Usia Dini Pada Masa Pandemi COVID-19 - Hesti Novita Sari; Kristiana Maryani; Isti Rusdiyani (UIN Sultan Maulana Hasanudin Banten, 2022)
The purpose of this study was to determine: (1) the nutritional intake of children aged 3 – 4 years during the covid-19 pandemic in Kubangawan Village, (2) ways parents provide nutritious food to chidren aged 3 – 4 tahun, (3) Factors that affect children who have malnutrition. This research is a qualitative research using descriptive. The subject in this study were the head of nutrition at the Ciruas public health center, parents of children aged 3 – 4 years. In the process of collecting data the researches used the metod of interview, observation, and documentation. While the validity test of the data used in the study were the persistence/consistency of observation, triangulation and member check. From the result of the study, it can be concluded that the nutritional intake or food that is often given to children aged 3 – 4 years is 4 healthy 5 perfect.